Meta-analisis Kemampuan Kognitif Siswa dalam Pembelajaran Fisika dengan Model Problem Based Learning (PBL) - Analiatus Shofiyah; Suprianto; Riskiyana Vajari; Moh. Nawafil Zain Robiz (Mutiara: Jurnal Ilmiah Multidisiplin Indonesia, 2024)
Physics education in schools often faces challenges in terms of student engagement and understanding due to the abstract nature of the concepts and the high analytical skills required. Conventional, non-interactive teaching approaches tend to be ineffective in addressing these issues. This study aims to evaluate the effectiveness of the Problem Based Learning (PBL) model in enhancing students’ cognitive abilities in learning Physics through a meta-analysis. The PBL model emphasizes student-centered learning, where students are invited to solve real and relevant problems, thus increasing engagement and deeper conceptual understanding. Data were collected from 20 research articles published between 2017 and 2024, which discuss students’ cognitive abilities and the PBL approach. The meta-analysis results show that PBL has a significant effect on improving students’ cognitive abilities in Physics, with 13 articles showing high effect sizes, 3 articles moderate effect sizes, and 4 articles low effect sizes. PBL has proven effective in developing students’ critical, creative, and analytical thinking skills. Additionally, PBL enhances students’ active participation in the learning process and facilitates the understanding and application of Physics concepts in various practical situations. This study asserts that PBL is an effective method for improving students’ cognitive abilities in learning Physics at the high school level, by fostering critical thinking, communication, and practical knowledge application skills. These findings underscore the importance of using innovative learning models such as PBL to advance Physics education and improve student learning outcomes.